Are gender and life attitudes associated with the wish to die in older psychiatric and somatic inpatients? An explorative study. (October 2014) - Bonnewyn, Anke; Shah, Ajit; Bruffaerts, Ronny; Demyttenaere, Koen
ABSTRACT Background: Death wishes are not uncommon in older persons, and to date, several risk factors have been identified. The presence of these risk factors is insufficient to fully understand why some older people, who are exposed to them, develop a wish to die and why others do not. The purpose of the study was to explore whether Purpose in Life as well as other life attitudes are associated with a death wish in older males and females. Methods: The sample comprised 113 older inpatients (from a psychiatric and somatic ward) with a mean age of 74 years. Psychiatric diagnoses were assessed by the SCID-II. Logistic regression analyses estimated the unique contribution of (the interaction between) life attitudes and gender to the wish to die, controlling for sociodemographic variables, depressive disorder, and somatic symptoms. Results: We observed a statistically significant relationship between life attitudes and the wish to die. Purpose in Life and the Purpose in Life*Gender interaction explained significant additional variance in the prediction of the wish to die. Purposelessness in life might therefore be an important correlate of a wish to die, especially in older men, independently from sociodemographic and clinical features. Conclusions: In assessing a wish to die in older adults, life attitudes need to be taken into account, besides the presence of a depressive disorder and/or somatic health. More specifically, finding or maintaining a purpose in later life might be an important feature in the prevention of the wish to die, especially in male persons.